Neutrophil-lymphocyte ratio and platelet-lymphocyte ratio in hypertensive patients: A prospective cross-sectional study - Sudha S; Birunthavathi M; Mythili M; Sai Sailesh Kumar Goothy (Asian Journal of Medical Sciences)
Background: Long-term hypertension progresses to produce atherothrombotic disease. Chronic inflammation may contribute to epithelial dysfunction and atherogenesis and is associated with high blood pressure. Neutrophil-to-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) ratios are the predictors of the cardiovascular diseases. However, studies related to this context are sparse comparatively.